(untitled) (Sains Humanika, 2019)
This study is designed to present a web 2.0 application that provides multimedia and animated video known as GoAnimate.Com which has been used as a learning activity tool directly in Arabic teaching and learning (T&L) process. This activity was implemented in the class whereby the students were actively involved as practitioners and the teachers played the role as facilitators. The guidance to use GoAnimate.Com was explained to students by teachers before dividing them into groups. Each group were asked to prepare an animated video containing simple Arabic conversation using GoAnimate.Com application. Quantitative method was utilized to make this study successful by using the instrument of questioners prepared to identify students’ perception towards GoAnimate.Com application and their preference of using this application in Arabic T&L at University Malaysia Kelantan (UMK). The result of this study has indicated that student’s perception towards GoAnimate.Com application in learning Arabic is high with the overall mean score of 4.05. This study has shown that the usage of GoAnimate.Com can increase students’ engagement and involvement in learning Arabic. Nevertheless, it is hoped that the outcome of this study can provide an alternative approach and various strategies in Arabic T&L towards Education 4.0 in the Forth Industrial Revolution era (IR4.0).